The effect of slow deep breathing relaxation exercise on pain levels during and post chest tube removal after coronary artery bypass graft surgery - Mohamad I. Jarrah; Issa M. Hweidi; Sirin A. Al-Dolat; Hossam N. Alhawatmeh; Salwa M. Al-Obeisat; Lama I. Hweidi; Aysam I. Hweidi; Osama A. Alkouri (Elsevier, 2022)
Objectives: This study aimed to evaluate the effectiveness of slow deep breathing relaxation exercise (SDBRE) in reducing patients' pain levels during chest tube removal (CTR) post coronary artery bypass grafting (CABG) surgery. Methods: In 2019, fifty post-CABG patients were conveniently selected from a cardiac intensive care unit in Jordan's major referral heart institute. The patients were randomly assigned to either an intervention group or a control group. A total of 25 patients were assigned into the experimental group who received slow deep breathing relaxation Exercise (SDBRE) alongside the conventional care before CTR. The remaining 25 patients constituted the control group (50%) that had CTR following conventional care. The Visual Analogue Scale (VAS) was used to measure the participants' pain levels during three phases: before CTR (Time 1), 5-min post CTR (Time 2), and 15-min post CTR (Time 2) to compare the intervention effect between the two groups. Results: The data analysis findings for the control and intervention group of patients showed that there was a statistically significant decline in their pain level across time for both groups (H = 32.71, P < 0.01; H = 47.23, P < 0.01) respectively. The intervention group had significantly lower pain levels than the control group at Time 2 (3.50 [1.20, 5.30] vs. 7.90 [7.00, 9.00], P < 0.01) and Time 3 (0.00 [0.00, 1.30] vs. 3.60 [2.40, 4.10] P < 0.01). Conclusions: Using SDBRE during CTR is an effective technique for reducing pain which can minimize the need for analgesics and their associated adverse effects.